Corporate Governance Practices and Bank Performance: Evidence from Indian Banks - Bezawada, Brahmaiah (Indian Journal of Finance and Banking, 2020)
The study examines the corporate governance practices and analyzes the role of the board characteristics (size of the board, the composition of the board, and functioning of the board) on the performance and asset quality of banks. We use a sample of 34 commercial banks consisting of 19 public sector banks and 15 private sector banks from 2009 to 2018 accounting for 93 percent of the total banking industry in India. The study finds that busy directors and the number of meetings have a positive significance on bank performance. The percentage of independent directors and the percentage of busy directors influence a significant negative relationship on the net non-performing assets ratio. The board size and number of meetings are associated negatively with Tobin’s Q significantly and the percentage of busy directors is a significantly positive impact on Tobin’s Q. The board size has a significantly negative impact on bank performance. The research findings provide some insights into corporate governance to the RBI for considering appropriate policy guidelines on corporate governance in the banking industry in India. The paper adds to the existing literature on corporate governance mechanisms and banking industry performance.